2019
DOI: 10.1007/s10485-019-09563-z
|View full text |Cite
|
Sign up to set email alerts
|

Homotopical Algebra for Lie Algebroids

Abstract: We construct Quillen equivalent semi-model structures on the categories of dg-Lie algebroids and L∞-algebroids over a commutative dg-algebra in characteristic zero. This allows one to apply the usual methods of homotopical algebra to dg-Lie algebroids: for example, every Lie algebroid can be resolved by dg-Lie algebroids that arise from dg-Lie algebras, i.e. that have a null-homotopic anchor map. As an application, we show how Lie algebroid cohomology is represented by an object in the homotopy category of dg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Proof. For ordinary L ∞ -algebroids, without filtrations or curvature, this is proven in [Nui19a]. The proofs of loc.…”
Section: Homotopy Theory Of Curved Lie Algebroidsmentioning
confidence: 92%
See 2 more Smart Citations
“…Proof. For ordinary L ∞ -algebroids, without filtrations or curvature, this is proven in [Nui19a]. The proofs of loc.…”
Section: Homotopy Theory Of Curved Lie Algebroidsmentioning
confidence: 92%
“…Notice that Lie algebroids over a fixed base are not algebras over an operad, so that the usual methods of constructing a model structure on them do not quite work. In [Nui19a], the third author showed that Lie (or equivalently L ∞ ) algebroids carry a semimodel structure for which the weak equivalences are quasi-isomorphisms.…”
Section: Mod Grmentioning
confidence: 99%
See 1 more Smart Citation
“…The following is the main result of [18]: Using the simplicial structure from [24] and the fact that every object in g/LieAlgd dg A is fibrant, one finds that g/LieAlgd dg A is a genuine (combinatorial) model category. Definition 2.6.…”
Section: Introductionmentioning
confidence: 98%
“…], so the result follows from (a shift of) Lemma 3.10.3.2.Tame dg-Lie algebroids. The tame model structure on dg-A-modules can be transferred to a semi-model structure on dg-Lie algebroids, by[18, Remark 4.25]: Proposition 3.12. The category of dg-Lie algebroids over A carries the tame semimodel structure, in which a map is a weak equivalence (fibration) if and only if it is a tame weak equivalence (fibration).…”
mentioning
confidence: 99%